Age and type of first exposure to pornography: it matters for girls and boys - Marshall, Ethan A. (Deviant behavior, 2024)
The increase in youth and adult use of pornography has led to increased research on the possible effects and implications of such use. A few prior studies have examined the relationship between age at first exposure to pornography and related problems later in life, including more problematic use of pornography. The current study used a sample of 924 males and females at a university in the Southern United States to examine the relationship between age and type of first pornography exposure to problematic use of pornography in young adulthood. Results indicated significant relationships between age at first exposure, first exposure type, and problematic pornography use in young adulthood. The findings highlight the importance of early intervention around pornography exposure and the causes of intentional pornography use at early ages.